Technique and theoretical approach for quantifying the hygroscopicity of black-carbon-containing aerosol using a single particle soot photometer. (March 2015) - Schwarz, J.P.; Perring, A.E.; Markovic, M.Z.; Gao, R.S.; Ohata, S.; Langridge, J.; Law, D.; McLaughlin, R.; Fahey, D.W.
Abstract: A single particle soot photometer (SP2), an instrument that measures the optical size and refractory black carbon (BC) mass content of individual aerosol particles, was modified to include a compact humidification system, described here. This permits quantification of water uptake by BC-containing particles, an important process that can affect their optical properties and lifetime. A Mie and κ -Köhler theory framework was developed to relate measured humidity-dependent changes in BC aerosol optical size to the hygroscopicity parameter ( κ ) of the non-BC content in the particles (which is responsible for water uptake by these particles). Laboratory testing of this experimental and theoretical system with both homogeneous non-light-absorbing particles and BC-containing particles was carried out. Agreement between the theoretical predictions and laboratory measurements for the homogenous aerosols validates the experimental methodology. For BC with a 70-nm thick coating of ammonium sulfate, reasonable agreement (equivalent to ~20% in κ ) between measurements and theoretical predictions were observed over a span of RH from 70% to 90%. Two SP2s were configured to sample in parallel, one dry and one humidified, permitting continuous monitoring of water uptake by BC-containing aerosol. Operational refinements in SP2 setup to optimize the optical size measurement of BC-containing aerosol, and the consistency between the two SP2s are presented. This system was flown on the NASA DC8 research aircraft during the 2012 DC3 and 2013 SEAC4RS campaigns, providing engineering data included here that demonstrate the system׳s performance under challenging sampling conditions. Finally, SP2-scattering lookup tables used in the theoretical portions of this work are provided for reference. Abstract : Highlights: A single particle soot photometer (SP2) has been humidified. Humidification technique is described and performance is evaluated. Observations are modeled with mie and κ-Köhler theories. SP2 performance is optimized to allow high precision optical measurements. Hygroscopicity of materials internally mixed with BC can be determined. Thickly coated BC particles provide stronger constraint on κ.